2017
DOI: 10.18632/oncotarget.23310
|View full text |Cite
|
Sign up to set email alerts
|

The value of systemic inflammatory markers in identifying malignancy in mucinous pancreatic cystic neoplasms

Abstract: The treatment decision-making of mucinous pancreatic cystic neoplasm (PCN) has become a common clinical problem since the diagnostic accuracy of current tests in identifying malignancies in pancreatic cysts is limited. In this study, we aimed to validate the predictive value of systemic inflammatory factors in detecting malignant PCNs. Two hundred and forty-five patients with pathologically confirmed mucinous PCNs in a single Chinese institution were retrospectively analyzed. Receiver operating characteristic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…Some inflammatory indicators (NLR, PLR, and LMR) based on circulating blood cells can be used as a simple and convenient way to measure systemic inflammatory response and as an independent predictor of survival and prognosis in various malignant tumors, including pancreatic cancer (8)(9)(10). Recently, there has been much evidence that inflammatory indicators also play an important role in predicting benign and malignant PCNs (12,13,31). Our study discovered that LA had good discrimination efficiency between SCNs and MCNs with an AUC of 0.6765 and a diagnostic cutoff point of 65.45.…”
Section: Discussionmentioning
confidence: 99%
“…Some inflammatory indicators (NLR, PLR, and LMR) based on circulating blood cells can be used as a simple and convenient way to measure systemic inflammatory response and as an independent predictor of survival and prognosis in various malignant tumors, including pancreatic cancer (8)(9)(10). Recently, there has been much evidence that inflammatory indicators also play an important role in predicting benign and malignant PCNs (12,13,31). Our study discovered that LA had good discrimination efficiency between SCNs and MCNs with an AUC of 0.6765 and a diagnostic cutoff point of 65.45.…”
Section: Discussionmentioning
confidence: 99%
“…14 Two additional studies demonstrated that NLR was predictive of invasive carcinoma on univariate analysis in all mucinous pancreatic cystic neoplasms. 16,17 Because NLR was elevated in patients with invasive disease, we further evaluated NLR for its association with pathologic factors that separate the more indolent colloid carcinoma from the more aggressive tubular subtype. Our results did not show that NLR was able to differentiate between the colloid and tubular subtypes, nor was it associated with any other pathologic variables.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Studies have investigated the use of NLR as a biomarker in pancreatic cystic neoplasms, and previous data have suggested that NLR is predictive of invasive disease in patients with mucinous pancreatic cysts, including IPMN. [14][15][16][17] In this study, we sought to determine whether NLR was predictive of grade of dysplasia and invasive carcinoma in our cohort of patients who have undergone resection for IPMN. Additionally, we investigated whether NLR can preoperatively predict high-risk versus lowrisk lesions, and therefore, possibly help identify which patients should undergo surgical resection.…”
Section: Introductionmentioning
confidence: 99%
“…SIR parameters have been proposed as markers of malignancy in pancreatic cystic neoplasms. Thus, in 245 patients with mucinous cystic pancreatic neoplasms, NLR ≥ 1.96 was significantly (p < 0.001) associated with invasive carcinoma [47]. In 318 surgically treated patients with pancreatic cystic neoplasms, high NLR was significantly associated with malignant tumour by univariate analysis.…”
Section: Diagnostic Role Of Nlr In Pancreatic Tumoursmentioning
confidence: 92%
“…In mucinous cystic neoplasms, elevated PLR was shown to be significantly associated with presence of invasive carcinoma in 245 patients from Shanghai [47] and 318 patients from Singapore [48].…”
Section: Diagnostic Role Of Plr In Pancreatic Tumoursmentioning
confidence: 99%